Review of disaster response strategies for sustainable development in the wake of flood risks in Zimbabwe’s rural-urban settlements - Tirivangasi, Happy Mathew; Nyahunda, Louis; Mabila, Thembinkosi (Technium Social Sciences Journal, 2021)
This paper aims to review the disaster response strategies implemented by the Government of Zimbabwe to mitigate the effects of floods in between 2016 and 2019. The daunting impacts of climate change are manifesting through floods, hurricanes, heat waves and drought in Sub Saharan Africa. As such, Zimbabwe is on record of falling victim to floods caused by torrential rains. Floods that struck Zimbabwe had calamitous consequences recorded where hundreds of people died, thousands displaced, infrastructure was destroyed, and people left vulnerable to diseases. Despite the country’s participation in international and regional conventions that recognizes climate change impacts and the need to develop modest disaster preparedness and recovery plans, Zimbabwe has been crawling to proactively formulate and implement disaster recovery mechanisms. As such, the country has been ravaged by floods unprepared where reactive disaster response strategies would be ignited. Having said that, this paper examined how the Government of Zimbabwe responded to the unusual occurrences of flash floods in both rural and urban settlements. The empirical analysis is based largely on data from databases such as the national surveys and literature. This paper argues that there is a robust need for the country to invest in disaster risk and recovery plans and disaster early warning systems where communities are not ambushed by gruelling occurrence of floods and its associated risks.